Top tagging - Plehn, Tilman; Spannowsky, Michael (Arxiv, 2011)
Top tagging is a recent approach to identifying boosted hadronic top quarks. It avoids reconstructing individual top decay products and instead uses a jet algorithm to reconstruct the entire top decay. Quite generally, geometrically large jets including heavy particles (fat jets) can be analyzed on the level of their subjet constituents. LHC data will soon allow us to establish this new analysis method. We discuss different tagging algorithms, their critical QCD aspects, and currently available experimental results. For the development of taggers and their different applications this review should provide a firm theoretical and algorithmic background.
Gesehen am 29.09.2017